2019
DOI: 10.1590/1980-265x-tce-2016-0426
|View full text |Cite
|
Sign up to set email alerts
|

Primary Healthcare Management: What Is Discussed in the Literature

Abstract: Objective: to identify what is discussed in studies published in Brazilian and international literature in the last ten years on Primary Health Care management. Method: an integrative review with a search carried out from 2006 to 2016, in the SciELO®, LILACS®, Scopus®, PubMed® and CINAHL® databases in the Portuguese, English and Spanish languages. The review followed the steps: formulation of the research question, definition of the inclusion and exclusion criteria, identification and selection of the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 86 publications
(83 reference statements)
0
4
0
14
Order By: Relevance
“…The study of Henrique et al (2019) identified that the managers of the BHU surveyed demonstrated that they were not prepared for the function, both because of the fragility and distance with the practice of services identified in the courses that train professionals in the health area, as well as the lack of training and continuing education offered in service for managers, it generally affects learning-by-doing for these professionals when they take office. Even so, a literature review study indicates that the essential skills of primary care managers are the organization of the teamwork and the planning of the services action priorities (Pires, Vandresen, Machado, et al, 2019). PAHO (2017) guides the use of continuing education as a tool to develop professionals in areas that present these gaps in technical, programmatic, or management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Henrique et al (2019) identified that the managers of the BHU surveyed demonstrated that they were not prepared for the function, both because of the fragility and distance with the practice of services identified in the courses that train professionals in the health area, as well as the lack of training and continuing education offered in service for managers, it generally affects learning-by-doing for these professionals when they take office. Even so, a literature review study indicates that the essential skills of primary care managers are the organization of the teamwork and the planning of the services action priorities (Pires, Vandresen, Machado, et al, 2019). PAHO (2017) guides the use of continuing education as a tool to develop professionals in areas that present these gaps in technical, programmatic, or management.…”
Section: Discussionmentioning
confidence: 99%
“…Research that conducted a review of scientific literature on the management in primary care identified as essential competencies of managers: “communication, management teams, planning with priority setting, solving problem-solving, evaluation of performance and leadership” (Pires, Vandresen, Machado, et al, 2019, p. 8). Another study performed with the participation of managers of the Family Health Strategy (FHS) in a municipality in Rio de Janeiro also analyzed the skills needed for the primary care manager and identified three categories: leadership; resource and care management; and mobilization of cognitive and affective resources (Fernandes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Envolve inúmeras dimensões como gestão de pessoas, relacionada à gestão de relações de trabalho e da força de trabalho em número e qualificação; gestão de materiais e processos, referente a estrutura, fluxos organizacionais, processos de trabalho, materiais e equipamentos; e gestão financeira. 25 Além da sobrecarga de trabalho e carga horária, a implementação das atividades e do cuidado foi destacada como fragilidade durante o desenvolvimento da pesquisa. Relativo a isso, em estudo efetuado acerca do dimensionamento de enfermagem e do processo de trabalho em uma UBS do Centro-Oeste de São Paulo, evidenciou-se falta de recursos humanos, implicações para o processo de trabalho relacionado a monitoramento do sistema de informação e reorganização da abrangência do serviço de saúde.…”
Section: Discussionunclassified
“…In addition, when professionals reported HSIL diagnoses, there was also an association with adequate monitoring. This aspect can be linked to the growth of the organization and reach of the PHC services 29 , as well as to the increase in the coverage of the cytopathological exams 13,27 . However, this result can also indicate late diagnosis, resulting from a service with failed screening and insufficient quality.…”
Section: /15mentioning
confidence: 99%